Alpha-tocopherol nanodispersions: preparation, characterization and stability evaluation - Cheong, J.N.; Tan, C.P.; Man, Y.B.C.; Misran, M. (2008)
A top down approach based on emulsification-evaporation technique was used to prepare nanodispersion of Î±-tocopherol. Physicochemical properties of the prepared nanodispersions were investigated under combination of the processing parameters (pressure and cycle) and ratio of aqueous:organic. Storage study was performed for 3 months to evaluate the stability of all the prepared nanodispersions. The results showed that homogenization pressure have significant (P < 0.05) influence on the droplet diameter and size distribution. On the contrary, the processing cycle had not significant (P > 0.05) effect on the droplet diameter and size distribution of the prepared nanodispersion. Droplet diameters in the range of 90-120 nm were obtained for the prepared Î±-tocopherol nanodispersions. During storage duration, there were no significant (P > 0.05) changes in mean diameters while the concentrations of Î±-tocopherol were significantly (P < 0.05) reduced for all prepared nanodispersions. In general, it is shown that emulsification-evaporation technique can be used as a suitable technique for the production of Î±-tocopherol nanodispersions with narrow size distribution.